VIBROACOUSTIC DIAGNOSIS OF DIAMOND BURNISHING PROCESS - Vilor Lavrentyevich Zakovorotniy; Maxim Mikhaylovich Khanukayev (Advanced Engineering Research, 2013)
The problem on the dynamic configuration of the diamond smoothing through the vibroacoustic emission signal control accompanying processing is considered. The dynamic equations based on the analysis which shows that the changes of the gradient mechanical-and-physical properties on the workpiece surface lead to the changes in the spectral composition of the vibroacoustic emission signal are proposed. On this basis, a method of the tuning processing system for the dynamic parameter is offered. It permits to select rational values of diamond tip clamping force to the workpiece. Theoretically, on the basis of the analysis of the smoothing dynamic process frequency characteristics, it is shown that on converging of the tool tip and the workpiece, the gradient of the process mechanical-and-physical properties changes. As a result of the variational equation analysis, changing in the oscillation spectrum is observed. Theoretical ideas are supported by the experimental studies of the process vibration characteristics.